Validity and reliability of the brief form of the normative male alexithymia scale among Chinese patients after radical prostatectomy - F. Wang; X. Zhang; L. Huang; X. Zhang; W. Jie; X. Chang; Y. Chu; L. Wang; W. Jia; B. Zhang (Scientific Reports)
Abstract Alexithymia, a cognitive and emotional deficit characterized by difficulty in expressing emotions and identifying feelings, poses significant challenges in healthcare settings. Developing a reliable and valid tool to measure alexithymia in post-prostatectomy patients would not only aid healthcare professionals in identifying at-risk individuals but also facilitate early intervention and targeted support. This study aimed to translate the Brief Form of the Normative Male Alexithymia Scale (NMAS-BF) into Simplified Chinese, evaluate the reliability and validity of the Chinese version, and explore its influencing factors. The English version of the NMAS-BF was translated into Chinese according to Brislin’s translation guidelines. A survey was administered to 430 patients who had undergone radical prostatectomy across four tertiary-grade A hospitals in China. To assess test-retest reliability, 30 patients completed the survey twice. Data analysis was performed using SPSS 26.0 and AMOS 22.0. Exploratory and confirmatory factor analyses were conducted to evaluate the content validity, construct validity, reliability, and concurrent validity of the translated NMAS-BF. Additionally, Pearson’s correlation, t-tests, and analysis of variance (ANOVA) were used to identify factors influencing the NMAS-BF. The Cronbach’s alpha coefficient for the Chinese version of the NMAS-BF was 0.856. The intra-class correlation coefficient (ICC) for the total scale was 0.938, indicating good stability. Content validity was satisfactory, with exploratory factor analysis revealing a single-factor model that accounted for 58.965% of the variance. Confirmatory factor analysis (χ²/df = 1.371, RMSEA = 0.041) demonstrated acceptable construct validity. Statistically significant differences in alexithymia levels were observed across patients with varying educational levels, family residence, household monthly income, and number of children. Perceived stress, mutuality, social impact, and self-esteem were identified as significant factors influencing alexithymia. This study initially translated the Brief Form of the Normative Male Alexithymia Scale (NMAS-BF) into Chinese and demonstrated its psychometric validity for assessing alexithymia in patients post-radical prostatectomy. By identifying alexithymic patterns and their contributing factors, the research aims to improve emotional expression and enhance the mental well-being of Chinese patients undergoing this procedure. Furthermore, the factors identified in the Chinese version of the NMAS-BF may provide valuable theoretical insights for future intervention studies.